If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + 1) = 5y + 17 Reorder the terms: 3(1 + y) = 5y + 17 (1 * 3 + y * 3) = 5y + 17 (3 + 3y) = 5y + 17 Reorder the terms: 3 + 3y = 17 + 5y Solving 3 + 3y = 17 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 3 + 3y + -5y = 17 + 5y + -5y Combine like terms: 3y + -5y = -2y 3 + -2y = 17 + 5y + -5y Combine like terms: 5y + -5y = 0 3 + -2y = 17 + 0 3 + -2y = 17 Add '-3' to each side of the equation. 3 + -3 + -2y = 17 + -3 Combine like terms: 3 + -3 = 0 0 + -2y = 17 + -3 -2y = 17 + -3 Combine like terms: 17 + -3 = 14 -2y = 14 Divide each side by '-2'. y = -7 Simplifying y = -7
| 2(5x-11)+7=3(x-7)-15 | | 1/4(5x-4)=3 | | -7x+7=9 | | 3.9x+5.37=-19.20 | | 7-18=z/-5 | | .3(6)+.05x=.15(36+x) | | x(.1)+x=210000 | | 2.8(1+0.5x)=-7 | | x(.1)+x=262500 | | y=pc | | 262500=x+x(.1) | | 5(3x-7)-14x=8 | | 8m+14m=198 | | -13=3+4y | | -(4y+2)-(-3y-6)=-3 | | -(4y+2)-(3y-6)=-3 | | 6(a-7)+18=3(a-4) | | 14(v+3)-2v=4(3v+3)-20 | | 9i/-3+8i | | -5y^2+20=0 | | 5y-12=27 | | 7z+4-3z=46-3z | | 3c^2-24c=0 | | 4.7q-5.6-4.3q=-0.6q-1.4 | | 8x+1=7x | | 6x^3-10x^2+12x-21=0 | | (n-5)(n+12)=0 | | 3(1+c)=2(c-3) | | 3w^2-22w=16 | | 10(8c-1)-18=78c+10 | | 19x+(-8)=-44+10x | | 4/a=b/2 |